Potensi Isolat Kamir Filosfer Buah Cabai sebagai Antagonis Terhadap Patogen Antraknosa - Ahmad Sulaiman; Fadjar Rianto; Sarbino Sarbino (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
Anthracnose disease in chili is caused by C. acutatum. This disease can cause a decrease in quality and production of chili pepper. The use of biological control agents can be an alternative in controlling of C. acutatum. The use of biological agents is more environmentally friendly and reduces the negative effects of synthetic pesticides. This study aims to obtain yeast isolates from the phyllosphere that have the potential to suppress anthracnose disease. The research was carried out at the Laboratory of Diseases at the Faculty of Agriculture, Tanjungpura University, Pontianak from July to October 2019. Yeast isolation used a pouring plate method on the media YGCA after the yeast on the fruit surface was enriched in liquid media YGC during 24 hours. Yeast antagonism test against C. acutatum using the dual culture method, conidia viability, and the ability of pathogens to infect fruit. The results of the isolation obtained 8 yeast isolates in healthy chili of Gada variety. Antagonism test obtained 3 yeast isolates with the highest inhibitory to C. acutatum growth, isolates K2, K3 and K5. Inhibition is greater than 50%. Based on the severity index of the disease in the hypovirulent test, the three yeast isolates were not pathogenic. In the in vivo test with the immersion method, both using yeast cells and filtrate showed that yeast cells could inhibit the growth of C. acutatum infection ability better than yeast filtrate. All yeast isolates can suppress the growth of C. acutatum with a different percentage of disease.